The effect of technopreneur orientation creation through sustainable fashion design curriculum / Rahayu Purnama - Purnama, Rahayu (2023)
The textile and apparel industries involved the manufacturing sector with the highest growth that had contributed significantly to the Indonesia's economic growth. Fast fashion has recorded as the highest demand among today's consumers in Indonesia. On the contrary, fast fashion has given a severe environmental impact to the Indonesia’s eco-system. Meanwhile, the fashion industry requires technopreneurs who engage in technology-oriented entrepreneurship to develop fashion designs that meet the Industrial Revolution 5.0 while resolving technological and digitalization-based complexities arising from this era. This fashion design technopreneur has the opportunity to become a sustainable and resilient graduate in facing the apparel industry in the future. Therefore, fashion education should be able to innovate in preparing its graduates to compete with the rapid technological advances and the demands of the apparel industry. However, based on several tracer studies in fashion education, preliminary studies, and statements of experts in the fashion field, these indicated that it is crucial to develop an entrepreneurship curriculum based on technology (technopreneur). This study explored the need for technopreneur orientation in creation toward a sustainable fashion design curriculum. Ultimately this will assist graduates to create job opportunities through technopreneur orientation.